Mortality in individuals with disruptive behavior disorders diagnosed by specialist services – A nationwide cohort study. (May 2017) - Scott, James G.; Giørtz Pedersen, Marianne; Erskine, Holly E.; Bikic, Aida; Demontis, Ditte; McGrath, John J.; Dalsgaard, Søren
Abstract: Disruptive behavior disorders (DBDs), inclusive of oppositional defiant disorder (ODD) and conduct disorder (CD), are associated with outcomes likely to increase risk of mortality. Using Danish National Registers, a total of 1.92 million individuals including 9495 individuals with DBDs diagnosed by specialist services were followed from their first birthday to 2013. Those with and without DBDs were compared using mortality rate ratios (MRRs) estimated using Poisson regression and adjusted for calendar period, age, sex, family history of psychiatric disorders, maternal age at time of birth, paternal age at time of birth, parental education status, and parental employment status. Over the course of follow up, which totalled 24.9 million person-years, 5580 cohort members died including 78 individuals with DBDs. The mortality rate per 10, 000 person-years was 9.66 for individuals with DBDs compared to 2.22 for those with no diagnosis. This corresponded to a fully adjusted MRR of 2.57 (95% confidence interval 2.04–3.20). Comorbid substance use disorder and attention-deficit/hyperactivity disorder resulted in the highest MRR across all categories. These findings demonstrate the excess mortality associated with DBDs. Highlights: First national-level study reporting the association between DBDs and mortality. Individuals with DBDs had a two and half fold increased risk of mortality. Those with comorbid substance use disorder and ADHD had the highest mortality.